PERENCANAAN STRUKTUR ATAS JEMBATAN BETON BERTULANG DENGAN MENGGUNAKAN BEBAN GEMPA SNI 1726-2019 DIKOTA BALIKPAPAN - Sakulok, Julianto Pipin; M. Shofwan Donny C; Rahayu, Yoanita Eka; Intan, Reynaldo Pratama (Universitas Widya Kartika Surabaya, 2024)
A bridge is a land transportation infrastructure that can be passed by vehicles or pedestrians tocross difficult terrain such as rivers, lakes, highways, railways, and so on. This bridgeconstruction project is a very important work in the transportation flow of the people of WestBalikpapan District in particular. This certainly affects the economic growth of the localcommunity. This activity can run well if the existing infrastructure is also in good condition. Inplanning the upper structure of this bridge, an analysis was carried out on the strength of theupper structure of the reinforced concrete bridge against loads based on SNI 1725-2016concerning loading for bridges, and earthquake loads in accordance with SNI 1726-2019 whichregulates earthquake resistance planning procedures for building and non-building structures.After calculations and evaluations were carried out on the backrest pile planning, 4Ø8 bendingreinforcement was used and sliding reinforcement was used Ø8 - 100 mm. In the planning of thebridge floor cantilever plate, with an arm length of 85 cm and a plate thickness of 20 cm, D13 -100 mm reinforcement is used. in the inner plate planning (Inner Slab) headed x-directionbending reinforcement used D29 - 150 mm. Y-direction bending reinforcement is used D29 -150 mm. In girder planning, girder height (h) 80 cm, width (b) 40 cm, T-Girder wingspan (beff)2300 mm, effective height T-Girder 650 mm. Bending reinforcement is used 10D32 withcompressive reinforcement is used 3D32. Shear reinforcement D12-150 mm. Plus shrinkagereinforcement to strengthen the structure, 3D12 is used. On the planning of the diaphragm,dimensions are planned 40 x 40 cm, 6D16 bending reinforcement is used. Given D12-150 mmsliding reinforcement as a fastener.